Service-orientation and teaching quality: business degree students’ expectations of effective teaching - Muhammad, Kashif; Hiram, Ting (Emerald Group Publishing Limited, 2014)
Purpose – Higher education teaching is analogous to delivering services in various business sectors. Students are regarded as customers of universities having specific needs and wants, which, if well recognized, can lead to creating delightful student experiences. This paper aims to identify the core ideas about excellent teaching in business schools which faculty members may notice in order to achieve excellence in teaching. Design/methodology/approach – The study is epistemologically framed to focus on interpretivism. The qualitative data have been collected from 30 business degree students, following a naturalistic paradigm. The case study method has been employed to conduct face-to-face interviews. Findings – The results revealed five core themes pertaining to teaching excellence in business education. These include; communication style, knowledge, positive attitude, creative work, and courtesy of the instructor as postulated by the students. Originality/value – The insights are purposeful and contribute substantially to theory development in the area of service-oriented teaching delivery in business education.